ICTs and rural development in India - Nirvikar Singh (University of California, Economics Department, 2006)
This monograph compares the methodologies and progress of the different existing models of information and communication technology (ICT) use for broad-based development and economic growth in India. It will examine the role of complementary reforms in government administration and policies. The focus is chiefly on the rural economy, where the developmental needs are the greatest, and the use of ICTs presents the most challenges. It examines the nature of benefits in areas such as education, health, market efficiency, and democratic participation, the channels through which impacts can be realized, and the practical means for realizing potential benefits, including organizational innovations and government policy as well as structural changes.
Keywords: O12; O3; L31; P2; 330; India; ICTs; Internet; development; Informationstechnik; Wirtschaftswachstum; Ländliche Entwicklung; Indien